Teaching International Relations in Post-Pandemic Era: The Case of Universitas Islam Indonesia: english - Haripa, Tri Inov; Majiid, Farhan Abdul (UII, 2025)
The Covid-19 pandemic presented both opportunities and challenges in higher education, including in the field of International Relations. On one hand, Covid-19 accelerated digitalization, encompassing online classrooms, online assignments, and blended learning with synchronous and asynchronous modes of instruction. This research will explore the process through which the Department of International Relations at Universitas Islam Indonesia adapted to the challenges posed by the pandemic. The study will employ a qualitative method, utilizing open-ended questions and interviews with lecturers from the Department of International Relations at Universitas Islam Indonesia. The data will be analyzed using Historical Sequence Analysis as developed by Mahoney et al. (2009). This research will demonstrate that the Covid-19 pandemic and digitalization are interdependent in establishing the new blended learning mode, which continues to be utilized to this day.